Efficient Ammonium Ion Removal from the State Company of Fertilizers Wastewater through Nano Zeolite Treatment - Aseel Tami Abduljabbar; Saadiyah Ahmed Dhahir; Muna Subhi Jamal (Iraqi Journal of Industrial Research)
One of the most significant environmental problems of the day is ammonium ion pollution of wastewater, especially from sources that produce chemical fertilizers. Higher ammonia concentrations in lakes and rivers increase eutrophication, lower dissolved oxygen levels, and ultimately cause the aquatic ecosystem to collapse. The adsorption method using one of the best adsorbent materials is one of the methods that can be used to remove ammonium ions from water with excellent results. This study aims to use adsorption technology with nano zeolite (NZ) to treat ammonium ion-contaminated water and simulate water release from the State Company of Fertilizers. The best conditions were discovered to be (2.5 gm) adsorbent dose, (240 min) shaking duration, (100 ppm) starting ammonium ion concentration at pH 8.0, and constant temp. 25oC for the efficient adsorption of NH4+ ammonium ions and effective removal onto NZ. The result shows that the parameters have great inﬂuence on the ammonium removal using the NZ if the removal rate reaches 98% and the maximum ammonium adsorption capacity (qe) obtained is 11.5 mg/g. The Freundlich model best describes the adsorption isotherms with a higher coefficient of determination (R2=0.97) than the Langmuir model with a coefficient of determination (R2=0.80). The results imply that the NZ is an efﬁcient adsorbent for ammonium ion removal.